Design and Optimization of a Hybrid Gas Generator for Hydrogen Peroxide Tank Pressurization - Mykhailo Vorobei; Mykola Bondarenko (Challenges and Issues of Modern Science)
Purpose. This study develops a pressurization system for hydrogen peroxide tanks using a hybrid gas generator powered by liquid oxygen and solid fuel. The system aims to improve hybrid rocket engine efficiency and reliability by stabilizing oxidizer tank pressure. Applications in space and defense are considered, where performance and safety are essential. Technical parameters and system efficiency are evaluated in terms of design, materials, and combustion processes. Design / Method / Approach. The study combines experimental methods and theoretical modeling to examine hybrid gas generator and pressurization system parameters. Thermal loads, tank pressure, and combustion reactions are modeled. Erosion and cooling efficiency are analyzed to assess durability. Findings. The system effectively maintains stable hydrogen peroxide tank pressure, ensuring continuous oxidizer supply. Ceramic coatings and heat-resistant materials reduce erosion, and liquid oxygen flow control optimizes combustion. Aluminum addition to the fuel boosts specific impulse by 25 seconds. Theoretical Implications. This research advances knowledge on hybrid systems in rocket engines and demonstrates hydrogen peroxide's efficiency as an oxidizer. Hybrid gas generators show promise in improving rocket system performance and reliability for space and defense applications. Practical Implications. The system may enable more reliable, reusable rocket engines for maneuvering and be applicable in commercial and scientific missions where safety and cost are priorities. Originality / Value. This study presents a novel hybrid gas generator approach using hydrogen peroxide, showing how innovative materials enhance rocket system reliability and efficiency. Results benefit engineers seeking to improve space and defense systems. Research Limitations / Future Research. Current work is confined to lab settings and theoretical analysis. Future research could explore real-condition experiments and cooling system optimization for extended use. Paper Type. Technical Note.